2010
DOI: 10.1111/j.1460-9568.2010.07339.x
|View full text |Cite
|
Sign up to set email alerts
|

AMPA receptor trafficking and learning

Abstract: In the last several years it has become clear that AMPA type glutamate neurotransmitter receptors are rapidly transported into and out of synapses to strengthen or weaken their function. The remarkable dynamics of AMPA receptor (AMPAR) synaptic localization provides a compelling mechanism for understanding the cellular basis of learning and memory, as well as disease states involving cognitive dysfunction. Here, we summarize the evidence for AMPAR trafficking as a mechanism underlying a variety of learned resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
83
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 80 publications
(212 reference statements)
2
83
0
1
Order By: Relevance
“…The diversity in regulation of AMPA receptor subunit expression suggests that changes in the properties of AMPA receptors serve specific functions in a variety of brain areas. Altering the level of AMPA receptor activity has also been shown to play an important role in dendritic patterning and synapse maturation and formation 2,3 , and disturbance of AMPA receptor localization has been implicated in many psychiatric and neurological disorders 4 . The dendritic targeting of AMPA receptors is therefore a crucial part of dendritic development and function.…”
mentioning
confidence: 99%
“…The diversity in regulation of AMPA receptor subunit expression suggests that changes in the properties of AMPA receptors serve specific functions in a variety of brain areas. Altering the level of AMPA receptor activity has also been shown to play an important role in dendritic patterning and synapse maturation and formation 2,3 , and disturbance of AMPA receptor localization has been implicated in many psychiatric and neurological disorders 4 . The dendritic targeting of AMPA receptors is therefore a crucial part of dendritic development and function.…”
mentioning
confidence: 99%
“…Analysis of the expression pattern of tGluA4 mRNA and its alternatively spliced isoforms showed that tGluA4 flip and flop were the most abundantly expressed variants in the adult turtle brain, followed by tGluA4c flip and flop and a novel variant that is truncated at the C-terminal end, tGluA4trc1. Here, we were interested in determining whether these alternatively spliced isoforms of tGluA4 were differentially regulated in an in vitro model of classical conditioning (Keifer and Zheng 2010).…”
mentioning
confidence: 99%
“…It is widely accepted that trafficking of AMPARs mediates rapid synaptic modifications underlying long-term potentiation (LTP), long-term depression, and learning (Derkach et al 2007;Keifer and Zheng 2010). Previously, we developed an in vitro brain stem preparation from the turtle, which generates a neural analog of eyeblink classical conditioning in which to study the cellular and molecular mechanisms of this form of learning [see Keifer et al (1995), Keifer and Houk (2011), and Keifer and Zheng (2010) for reviews].…”
mentioning
confidence: 99%
See 2 more Smart Citations